Efficient use of information and social value of information - George-Marios Angeletos; Alessandro Pavan (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2006)
This paper analyzes equlibrium and welfare for a tractable class of economies (games) with externalities, strategic complementarity or substitutability, and heterogenous information. First, we characterize the equilibrium use of information; complementarity heightens the sensitivity of equilibrium actions to public information, raising aggregate volatility, whereas substitutability heightens the sensitivity to private information, cross-sectional dispersion. Next, we define and characterize an efficiency benchmark designed to address whether the equilibrium use of information is optimal from a social perspective; the efficient use of information reflects the social value of aligning choices across agents. Finally, we examine the comparative statics of equilibrium welfare with respect to the information structure; the social value of information is best understood by classifying economies according to the inefficiency, if any, in the equilibrium use of information. We conclude with a few applications, including production externalities, beauty contests, business cycles, and large Cournot and Bertrand games.
Keywords: C72; D62; D82; 330; incomplete information; coordination; complementarities; externalities; amplification; efficiency; Informationsökonomik; Spieltheorie; Informationswert; Theorie